“MORAD ESCAPE”, a novel research-based escape room approach for evaluating research competencies of health professions students - Arvin Mirshahi; Ali Khanipour-Kencha; Sogol Keyvanpour; Maryam Karbasi Motlagh (BMC Medical Education)
Abstract Background Escape rooms offer an engaging platform to assess skills such as information retrieval, teamwork, leadership, and learning processes. Beyond their educational utility, escape rooms serve as a valuable system for complementing traditional evaluation methods. They provide a dual role as both an innovative educational and assessment tool, offering a novel approach to fostering and evaluating essential competencies. Research skills, particularly vital in medical sciences, require such innovative evaluation approaches. This study aimed to assess the research competencies of students at Tehran University of Medical Sciences using a research-based escape room. Methods This sequential exploratory mixed-methods study was conducted in three phases: design, implementation, and evaluation, between February 29, 2024, and July 1, 2024. The escape room was designed using the EscapED model, involving a literature review, expert input, and the development of two tools: a research competency checklist and a game evaluation scale. After piloting, 60 eligible medical students (12 groups of five) voluntarily participated in the activity, conducted over two days with six 90-minute sessions per day. The evaluation phase assessed game design and team performance using the validated tools. Results Following validation and reliability testing of the tools, 60 participants (mean age 21.05 ± 1.65 years; 58.45% male, 41.6% female) completed the activity. Most were undergraduates (91.6%) and medical students (81.6%). The mean raw score on the research competency checklist was 336 ± 137.1 (range: 112.5–500). Negative scores averaged 38.8 ± 20.9, and final scores averaged 298 ± 150.1 (range: 42.5–485). The top three teams received research grants as prizes. The escape room was rated 3.7 ± 0.31 (out of 5) for overall experience, highlighting its effectiveness as an assessment tool. Conclusions This study demonstrates the potential of escape rooms as dynamic tools for assessing research competencies in medical sciences education. Integrating gamified learning with structured evaluation frameworks and incentives fosters engagement and provides an innovative alternative to traditional assessments. Further studies should explore the scalability and adaptability of this approach in broader educational contexts.